Hsp90, DnaK, and ClpB collaborate in protein reactivation - Joel R. Hoskins; Anushka C. Wickramaratne; Connor P. Jewell; Lisa M. Jenkins; Sue Wickner (Proceedings of the National Academy of Sciences, 2025)
Hsp70, Hsp90, and ClpB/Hsp100 are molecular chaperones that help regulate proteostasis. Bacterial and yeast Hsp70s and their cochaperones function synergistically with Hsp90s to reactivate inactive and aggregated proteins by a mechanism that requires a direct interaction between Hsp90 and Hsp70 both in vitro and in vivo. Escherichia coli and yeast Hsp70s also collaborate in bichaperone systems with ClpB and Hsp104, respectively, to disaggregate and reactivate aggregated proteins and amyloids such as prions. These collaborations are dependent on direct interactions between ClpB/Hsp104 and Hsp70. We explored the possibility that E. coli homologs of Hsp70, Hsp90, and ClpB, referred to as DnaK, Hsp90 Ec , and ClpB, respectively, in combination with two DnaK cochaperones, DnaJ and GrpE, could promote protein disaggregation and reactivation under conditions where bichaperone systems are ineffective. Our results show that Hsp90 Ec is able to overcome the inhibition of protein disaggregation and reactivation observed when the concentration of DnaK is approaching physiological concentrations. We found that ATP hydrolysis and substrate binding by all three chaperones are essential for the collaborative function. The work further shows that ClpB acts early in protein reactivation with DnaK and its cochaperones; E. coli Hsp90 acts at a later stage after ClpB. The results highlight the collaboration among chaperones to regulate and maintain proteostasis.